The System Design of Payroll Accounting Information System at Private Primary School in East Jakarta - Putri, Yayang Novealita Wahono; Riwajanti, Nur Indah; Eltivia, Nurafni (PT. EQUATOR SINAR AKADEMIA, 2024)
This research aims to design a system design of payroll Accounting Information System (AIS) at a primary private school (Madrasah Ibtidaiyah Al-Baidlo/”MIAB”), East Jakarta to improve the efficiency of payroll business processes. Business Process Improvement was used as a design approach in this research, with an applied research type. Collect data by interview with Headmaster and Treasurer. The tool used to document business processes is the Bizagi Modeler. Automation is carried out to prevent human error and increase the processing speed of payroll business processes. The business processes that are designed will be tested by material and information technology experts. The result of this research is that the proposed (to-be) business process increases the simplification of payroll activities by improving the quality of fast and accurate decision making which has economic value. Using Business Process Modelling Notation allows this research to present proposed business processes related to needs and solutions to problems in the research objects observed. This research is proven to be able to increase the simplification of business processes, increase efficiency in decision making by school principals in a relatively short time from 337 minutes to 41 minutes or a time saving of around 296 minutes (equivalent to 4.93 hours).Cutting manual activities to automated processes increases the opportunity for fraud and human error.